2011
DOI: 10.1186/1475-2859-10-93
|View full text |Cite
|
Sign up to set email alerts
|

Protein trafficking, ergosterol biosynthesis and membrane physics impact recombinant protein secretion in Pichia pastoris

Abstract: BackgroundThe increasing availability of 'omics' databases provide important platforms for yeast engineering strategies since they offer a lot of information on the physiology of the cells under diverse growth conditions, including environmental stresses. Notably, only a few of these approaches have considered a performance under recombinant protein production conditions. Recently, we have identified a beneficial effect of low oxygen availability on the expression of a human Fab fragment in Pichia pastoris. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 65 publications
4
38
0
Order By: Relevance
“…However, co-expression of the helper gene could also compete with the target gene for transcription. Baumann et al reported that the reporter gene mRNA levels among the recombinant protein production improved strains of overexpressing helper genes were similar to the reference strain (Baumann et al 2011). In our research, the transcriptional level of PGUS was decreased when the helper gene TPX was overexpressed.…”
Section: Discussionsupporting
confidence: 54%
“…However, co-expression of the helper gene could also compete with the target gene for transcription. Baumann et al reported that the reporter gene mRNA levels among the recombinant protein production improved strains of overexpressing helper genes were similar to the reference strain (Baumann et al 2011). In our research, the transcriptional level of PGUS was decreased when the helper gene TPX was overexpressed.…”
Section: Discussionsupporting
confidence: 54%
“…This phenomenon was unexpected, because increased protein production will demand more ATP and reduction power in the form of NADPH. Although proteome data and actual metabolic activities were well in agreement in a study using recombinant P. pastoris (45), this is not generally true for S. cerevisiae (46 -47). However, a reduction of TCA cycle fluxes has been described for a human superoxide dismutase producing S. cerevisiae strain (48).…”
Section: Discussionmentioning
confidence: 83%
“…Manipulation of cellular membrane by addition of surfactants has been shown to improve protein secretion in S. pombe (11). The decrease of ergosterol levels by addition of the fungicide fluconazole has been shown to enhance protein secretion in P. pastoris (45). Addition of fluconazole to S. pombe NW10 decreased ergosterol levels by more than 30% whereas at the same time improving maltase secretion 1.3-fold.…”
Section: Discussionmentioning
confidence: 99%
“…This nonionic surfactant enhances TP3 binding to bacterial cells by increasing membrane fluidity and therefore influences the position of the viable population in the SSC-FL4 dotplot. 18 It must be noted that despite the advantages of FCM, the technique also has its drawbacks compared with VPC. Although the latter is cost-effective and easy to perform, skilled technicians are needed to operate the flow cytometer and interpret the often complex data.…”
Section: Discussionmentioning
confidence: 99%